1998
DOI: 10.1128/jcm.36.4.931-936.1998
|View full text |Cite
|
Sign up to set email alerts
|

Use of Immunoblot Assay To Define Serum Antibody Patterns Associated with Helicobacter pylori Infection and with H. pylori -Related Ulcers

Abstract: Serology has been used worldwide to detect Helicobacter pylori infection. Using an immunoblot assay with an antigen from strain ATCC 43579, we sought to determine the antibodies which were good markers of colonization and the antibody patterns associated with ulcers or atrophy. Out of 98 dyspeptic patients, 41 were colonized byH. pylori, based on a positive culture or on positive results of both a urease test and direct examination. These 41 patients were seropositive by an enzyme immunoassay, and 12 of them h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…pylori infection can lead to a variety of diseases. At present, the only way to identify the illness associated with H. pylori infection is by an endoscopy examination, together with histologic examination of the gastric mucosa [20]. The prevalence of the cagA gene and vacA alleles amongst Spanish H. pylori clinical isolates increased with age, and was more frequent in older patients than in younger.…”
Section: Discussionmentioning
confidence: 99%
“…pylori infection can lead to a variety of diseases. At present, the only way to identify the illness associated with H. pylori infection is by an endoscopy examination, together with histologic examination of the gastric mucosa [20]. The prevalence of the cagA gene and vacA alleles amongst Spanish H. pylori clinical isolates increased with age, and was more frequent in older patients than in younger.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17] A low-molecular-weight protein has also been found to be associated with peptic ulcer disease. [18][19][20] Although preliminary studies have failed to detect an association between VacA, CagA and the 35-kDa protein and non-ulcer dyspepsia, 21,22 these studies were limited by the small numbers of patients or a lack of healthy controls. 19,22 Clinical trials employing eradication therapy in patients with non-ulcer dyspepsia may provide new insights into the association between infection with specific H. pylori strains and non-ulcer dyspepsia, by detecting the pre-treatment immunoglobulin G (IgG) antibody responses to specific virulence factors of H. pylori.…”
Section: Introductionmentioning
confidence: 99%
“…Helicobacter pylori is recognized as a major cause of gastritis and peptic ulcer and a key factor in the development of gastric cancer, gastric lymphoma and non-ulcerative dyspepsia in man (Karvar et al 1997). Strains carrying the genes encoding the cytotoxin-associated protein (cagA) are associated with duodenal ulcers and gastric cancer (Aucher et al 1998). Patients infected with these organisms have been shown to produce serum antibodies to H. pylori antigens and several studies have implied that the immune response correlates with the histological ®ndings in biopsy specimens (Drumm et al 1990;Aguirre et al 1992;Schembri et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Serological studies have shown that strains carrying the cagA gene are more often associated with severe gastroduodenal outcomes such as peptic ulcer disease (PUD) and distal adenocarcinoma (Aucher et al 1998). Several studies have reported that CagA-producing strains account for > 90% of H. pylori isolates from humans in developing countries, compared with only approx.…”
Section: Introductionmentioning
confidence: 99%